DISPUTES JUSTICE, UTILIZATION, AND LEGAL CERTAINTY IN THE PRIVATIZATION OF WATER RESOURCES - Wadi, Husnan (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
Justice is like water that never dry to talk,  especially when it touches on basic necessities that inseparable from the lives of both humans and other biological organisms. Privatization by investors when correlated with the law sometimes has problems of its own. How justice should be placed by not forgetting one of the most important elements of life. Will law Number 7 Year 2004 and the Constitution Year 1945 of NRI,  how social justice and certainty to be guaranteed by the state if things become a basic need of human needs that are privatized by investors ?. Retribution is not balanced will pawn justice values that are not organized into an opportunity for abuse than the underlying regulatory law subjects freedom in getting added value for the few. Justice,  expediency and certainty is not to negate the one with the other giving rise to the other victim.Key Word: Privatization,  Water and Law